The geographic scope of the svalbard treaty and norwegian sovereignty: historic - or evolutionary - interpretation? - Ørebech, Peter Th (Faculty of Law, University of Zagreb, 2017)
The Svalbard Treaty and its claimed ‘extended-reach’ jurisdiction incorporating both the continental shelf and exclusive economic zone (EEZ) – ie a fisheries protection zone (FPZ) – is an international law puzzle. Disputes regarding the Treaty’s jurisdictione ratione terrae results from interpretative differences. My findings are as follows: the Treaty’s concept of ‘full and absolute sovereignty’ refers to the one-time jurisdiction transfer that occurred in April 1925. The notion of ‘territorial waters’ attracts both an historic (static) and evolutionary (dynamic) reading. Regarding its material content, we are faced with the first category. Considering geographic reach, evolutionary reading takes over. ‘Territorial water’ jurisdictione ratione terrae is a generic form whose reach, which is at most 12 nautical miles, is dynamic. The treaty does not prevent Norway from unilaterally deciding whether to enforce this maximum, or a less extensive, area. While territorial sea jurisdiction due to the development of international law may extend to 12 nautical miles, it cannot creep to 200 nautical miles. Due to substantial variations, the EEZ cannot qualify as a similar zone adjoining the territorial sea. Further; it is difficult to argue that its reach should include areas beyond the territorial sea of Svalbard due to the very fact that its reach is limited to the ‘Svalbard Box’. Coastal state jurisdiction beyond the Box is not granted in the Svalbard Treaty but results from the 1982 Law of the Sea Convention (LOSC)